Emotional intelligence and aggression: The moderator role of gender. - Peláez-Fernández, María Ángeles; Extremera-Pacheco, Natalio; Fernández-Berrocal, Pablo (My University, 2012)
Recent research has indicated that Emotional Intelligence (EI) is associated with aggression. However, this relationship has been mainly demonstrated among adolescents and by means of self-report questionnaires, which is associated with bias related to shared-reported variance. Based in previous research that found gender differences in the relationship between EI and relevant social and health outcomes, the current study aimed to examine the moderator role of gender in the EI-aggression relationship. Participants were 296 young adults who completed an ability measure of EI, as well as an aggression inventory that’s assesses individual´s behavior in response to provoking scenarios. Results confirmed gender differences in ability EI, with higher levels in women compared to men. Next, interaction analyzes showed that gender moderated the ability EI-aggression relationship. High levels of ability EI were related to higher levels of assertiveness and feelings of irritation in men, but not in women. High levels of ability EI were related to lower levels of anger in women, but not in men. We suggest explanations for these differences between the genders. We also discussed the importance of incorporating gender differences in both theoretical and empirical studies investigating ability EI.
Keywords: Inteligencia emocional; Agresividad (Psicología); Diferencias sexuales (Psicología); Emotional intelligence; MSCEIT; Aggresion; Moderation